Marie Luise Gotheins "Geschichte der Gartenkunst" Das Bild des Gartens als Text - Seeber, Karin (Heidelberg University Publishing (heiUP), 2020)
Marie Luise Gothein's "A History of Garden Art", first published in 1914 and still in print, was immediately recognized as a classic, but has so far never been brought into focus as a seminal work of the discipline. This thesis examines the cultural scientist's intellectual and aesthetic concepts that guided her in her description of garden art. What defining concepts did she have when presenting the ever-changing art work of the garden in text and image? What role does the reform garden movement play, which was in full swing at the time of publication? The analysis of Gothein's descriptions of gardens, such as Villa d'Este, shows how fundamentally historical writing is influenced by the challenges of the time. The volumes reflect an ecocritical human approach to the environment.;Marie Luise Gothein verfasste 1914 mit ihrer "Geschichte der Gartenkunst" einen Klassiker, der bis heute zwar übersetzt und neuaufgelegt, nie jedoch als Grundlagenwerk in den Fokus gerückt wurde. Diese Arbeit untersucht die intellektuellen und ästhetischen Konzepte der Autorin im Hinblick auf ihre Darstellung der Gartenkunst. Welchen Prämissen folgt die Kulturwissenschaftlerin bei der Fixierung des stets im Wandel begriffenen Raumkunstwerks Garten in Text und Bild? Welche Rolle spielt die Reformgartenbewegung, die zur Zeit der Veröffentlichung in vollem Gange war? Die Analyse von Gotheins Gartenbeschreibungen, etwa der Villa d'Este, zeigt, wie grundlegend die Geschichtsschreibung von den Herausforderungen der Zeit beeinflusst ist: Im Sinne des Ecocriticism spiegeln die Bände die Auseinandersetzung des Menschen mit seiner Umwelt.